PENGEMBANGAN ADSORBENT BED UNTUK PENINGKATAN KONDUKTIVITAS TERMAL MELALUI PENAMBAHAN PARTIKEL METAL ALUMINIUM - Didik Ariwibowo; Sutrisno Sutrisno (Gema Teknologi, 2015)
Didik Ariwibowo, Sutrisno, in this paper explain that this research is to increase thermal conductivity of a adsorbent bed by adding metal particles in it so that the bed become a granule-mixed bed. The adsorbent bed contains activated-carbon granule and aluminium particles. The research activity include: design and fabrication of adsorbent bed prototype following thermal performance study of the adsorbent bed. The thermal performance study of the adsorbent bed was conducted by varying metal/adsorbent ratio of 5%, 10%, 15% by volume. The result showed that adding 5%, 10%, and 15% aluminium particles into adsorbent bed has increased its thermal conductivity, those are 10,9 Wm-1K-1; 21,9 Wm-1K-1; and 30,9  Wm-1K-1 respectively from 1,6 Wm-1K-1 activated carbon thermal conductivity. The values of experimental thermal conductivity were higher than those of calculated thermal conductivity. The percentage of the difference between experimental thermal conductivity and calculated thermal conductivity decreased as bed surface temperature increased. The relatively higher percentage was in 45% whereas the lower was 10%. The lower range of the difference was 10-20% occurred in 55-65 oC temperature range. Key words: adsorbent bed, metal/adsorbent ratio, thermal conductivity